Initial Screening Results for Gonorrhea and Chlamydia in Pregnancy and the Association With Subsequent Test Results [A216]. (May 2022) - Kairis, Kelsey; Holbert, Michael; Von Hoene, Amanda; Mitchell, Ashley
Abstract : INTRODUCTION: Gonorrhea and chlamydia infections during pregnancy are associated with adverse perinatal outcomes. The Centers for Disease Control and Prevention recommends screening for gonorrhea and chlamydia at the first prenatal visit and again in the third trimester for high-risk patients. The objective of this study is to determine rates of subsequent positive gonorrhea/chlamydia tests in pregnant patients based on their initial screening results. METHODS: This is an institutional review board‒approved multicenter observational study including patients who delivered from January 1, 2014, to December 31, 2020, with more than one gonorrhea/chlamydia test during pregnancy. Patients whose initial tests were negative were compared with patients whose initial tests were positive. Fisher's test and multiple logistic regression were performed. RESULTS: There were 8, 163 pregnancies with multiple gonorrhea tests and 8, 213 pregnancies with multiple chlamydia tests. There was a significant difference in subsequent gonorrhea-positives in pregnancies with an initial positive test (33/194, 17.0%) compared to an initial negative test (10/7, 969, 0.1%); odds ratio (OR), 163.2; 95% CI, 76.5–378.2; P <.001. Likewise, there was a significant difference in subsequent chlamydia-positives in pregnancies with an initial positive test (266/1, 003, 26.5%) compared to an initial negative test (37/7, 210, 0.5%); OR, 69.9; 95% CI, 48.9–102.3; P <.001. These associations remained significant following logistic regression to control for confounders. CONCLUSION: Among pregnancies with an initial negative gonorrhea/chlamydia screening result, subsequent positive results were unlikely. This may be a simple differentiator for the need for subsequent testing in pregnancy, leading to significant cost savings.